Psychotic disorder due to methamphetamine use in a female case - Aydın Taslı, Begüm; Köse, Sefanur; Puşuroğlu, Meltem; Hocaoğlu, Çiçek (Journal of Dependence, 2023)
Methamphetamine is an amphetamine-derived drug that is frequently abused worldwide and has strong addictive effects.Chronic methamphetamine use leads to changes in dopaminergic receptor density after a while.It acts on dopaminergic systems, particularly in the mesolimbic system and striatum, resulting in sensitization and addiction.This change in the dopaminergic system may explain the psychotic symptoms. However, the mechanism of psychosis caused by methamphetamine and sex-specific features have not been fully elucidated. Studies in recent years have shown that methamphetamine and similar stimulants cause an increase in the incidence of schizophrenia and related disorders. Methamphetamine psychosis has a clinical presentation very similar to schizophrenia. Sometimes it is very difficult to distinguish them from each other. In this case report, we discuss a female case who developed psychotic disorder after a single use of methamphetamine.